Implications of Changes in the Criminal Procedure Law of the ITE Law on Individual Rights in the Indonesian Legal System - Sidiq, Fahmi; Azahra, Astrid Sulistya; Pirdaus, Dede Irman (International Journal of Humanities, Law, and Politics, 2024)
The revision of the Electronic Information and Transactions Law (UU ITE) in Indonesia has become a hot topic of debate. Institutions and activists such as the Institute for Criminal Justice Reform (ICJR) and the Press Legal Aid Institute (LBH Pers) have presented various arguments regarding the impact of these changes. This article outlines the five main arguments advanced by the ICJR and LBH Pers. First, there is an objection to Article 27 paragraph (3) which regulates insults and defamation. Second, changes in criminal procedural law raise concerns about the discretionary authority of law enforcement officials without involving the courts. Third, the addition of cyberbullying-related crimes raises concerns about the potential for over-criminalization. Fourth, governments are given additional powers to filter and block content, which can result in potential abuse. Finally, the fifth argument relates to the "right to be forgotten" clause which can be used as a tool of censorship against news publications and journalists about one's past. This article also examines the impact of information technology developments on computer crime and underscores the importance of protecting individual rights and free speech in the digital age.